JAX, THE ARCHITECTURE: Designing a Chatboat Architecture to Reduce Ajax Fancare’s Logistical Problem and Enhance Fan Experience - Steven Limandjaja (Institute of Research and Community Outreach - Petra Christian University, 2018)
This paper is the documentation of a graduation internship at Digital Society School (DSS) in which they teamed up with Ajax Fancare to solve their logistical problem and enhance the fan experience. Ajax Fancare is facing a logistical problem in manually answering every fan’s question via calls, emails, social media, or live chat. They believe that chatbot is the solution to this problem. The goal of this project is to research, design, and prototype a chatbot that could tackle the logistical problem and enhance the fan experience. The deliverable is a chatbot prototype and architecture in which Ajax Fancare could build upon for their future customer service chatbot. The main question of the research is answered by the chatbot architecture: Jax the Architecture, a conversational tree of all the possible interactions between a user and the chatbot. The final chatbot architecture answers the research question by mapping together the main elements of the chatbot such as the information fans needed from Ajax Fancare and additional features that create a new and inclusive experience. The prototypes and final chatbot architecture are ready to be tested for further research and serve as a cornerstone for future development of the Ajax Fancare chatbot.